The Role of Self-Esteem in Responding to Dating Violence: A Case Study of Dating Violence Victims - Nur Irmayanti; Fristy Oktaria Grahani; Aironi Zuroidah (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to analyze the impact of self-esteem (HD) on dating violence (DV) using simple linear regression analysis. The results show that there is a significant relationship between HD and DV, with an unstandardized regression coefficient of 0.992, meaning that every one-unit increase in HD is expected to cause a 0.992-unit increase in DV. Although this relationship is statistically significant, the correlation coefficient (R) of 0.310 indicates that the effect of HD on DV is relatively weak. This suggests that while there is a positive relationship between the two variables, the strength of the relationship is not substantial enough to have a major impact on DV. Previous research also shows similar findings, where the relationship is significant but weak. A limitation of this study lies in the use of a simple linear regression model that includes only one independent variable. Therefore, further research using multiple regression models is recommended, incorporating additional variables that may have a greater impact on DV. This study provides an initial understanding of the relationship between self-esteem and dating violence, but further development is needed to strengthen the findings.